Representasi Bahasa Isyarat dalam Film Hear Me: Our Summer, Analisis Interaksi Nonverbal dan Persepsi Penonton - Ramadhani, Nur Fatimah; Aufafatih, Shandy Rifqah; Darwis, Syarpina; anhar, Anhar (Indo-MathEdu Intellectuals Journal, 2025)
Communication is a fundamental process in human interaction that encompasses both verbal and nonverbal dimensions. One form of nonverbal communication that has increasingly gained attention is sign language, particularly through film media. This study aims to analyze the representation of sign language and audience perceptions of the film Hear Me: Our Summer. The method used is descriptive qualitative with techniques of observation, analysis, and documentation. Data were obtained through direct observation and systematic recording of the research object, as well as questionnaires administered to 100 respondents. The findings reveal that the film successfully represents sign language not as a barrier, but as a difference that should be respected. Thus, the film functions not only as entertainment but also as a medium to broaden public awareness of equality, empathy, and acceptance of diversity. However, the absence of voice interpreters in several scenes was perceived to reduce emotional depth. Overall, this study affirms the dual role of film as both entertainment and effective social advocacy in promoting inclusivity and inspiring sign language learning among Indonesian audiences.in learning sign language. difference that deserves appreciation. Moreover, the film inspires the audience to be more open-minded and motivated to learn sign language